Calcium phosphate bone cement/mesoporous bioactive glass composites for controlled growth factor delivery. (3rd February 2017) - Schumacher, M.; Reither, L.; Thomas, J.; Kampschulte, M.; Gbureck, U.; Lode, A.; Gelinsky, M.
Abstract : The composites of calcium phosphate bone cements and mesoporous bioactive glass allow the controlled, local delivery of growth factors into specific bone defects while maintaining their biologic activity. Abstract : Calcium phosphate (CaP) bone cements are widely used for the treatment of bone defects and have been proposed to serve as a delivery platform for therapeutic drugs, proteins and growth factors into the defect region. However, they lack sufficient porosity to allow immediate bone ingrowth and thus foster rapid integration into the bone tissue. In this study we investigated a composite prepared from a hydroxyapatite forming bone cement and mesoporous bioactive glass (MBG) granules as a potential carrier for biologically active proteins. The mechanical properties of the composite were not compromised by up to 10 wt% MBG granule addition, which can be attributed to the strong interface between the cement matrix and MBG particles, however this modification induced a significant increase in porosity within 3 weeks ageing in an aqueous liquid. The release profiles of two proteins, lysozyme and the vascular endothelial growth factor (VEGF), could be controlled when they were loaded onto MBG granules that were subsequently embedded into the cement when compared to direct loading into the cement precursor. Both proteins were also demonstrated to maintain their biologic activity during embedding and release from the composite. These findings suggest the CaP bone cement/MBG composite developed in this study as a potential delivery platform for growth factors or other bioactive substances.